The Discursive Space of the Cultural and the Political - Encarnacion Tadem, Teresa S. (Kasarinlan: Philippine Journal of Third World Studies, 2009)
One of the still underdeveloped aspects in understanding politics is the role of culture in shaping political concerns. The three articles in this issue attempt to address this by critiquing current cultural paradigms and offering new ones in analyzing democratization, development, political conflict, and the intertwining of nationalism and globalization, among others. This is what J. Shola Omotola attempts to do in his article, “Against the Cultural Gap Thesis on Africa’s Democratization.” The cultural gap thesis argues that diverse African polities and societies are, by their nature, hostile grounds for democracy. Omotola contests this position on two grounds. First, he does away with the notion that there is only one form of democracy and a congruent political culture to sustain it. Then he argues that Africa’s tumultuous relationship with democracy is not due to a natural misfit. Rather, it is a consequence of the continent’s tortured history of colonialism and a subsequent postcolonial era ruled by capital that prefers profit to freedom; a stable market propped up by an iron hand over a society that is humane and just. A democratization that disregards such history and cultural specificity will indeed fail. The importance of culture and history shaping politics is further seen in Yilmaz Çolak’s “Nationalism and the Political Use of History in Cyprus: Recent Developments.” A particular and pertinent dimension, which Çolak examines, is nationalism as understood in the politics of Cyprus’s history. Çolak points out that the historiographies of the Greek Cypriots and the Turkish Cypriots produce respective collective memories, which have structured possible solutions to the Cyprus Problem. Their history of conflict and divergent allegiances to external powers have made it difficult for the political leaders on both sides to imagine a nationalism that is able to make the connections between all the individual and the state. As argued by Çolak, “The two states of Cyprus have launched typical processes of forming national history that is exclusionary and prejudiced, rejecting the Other. That reflects a centrally engineered process of nation building which to some extent relies on selected past experiences as well as cognitive categories. The result is the prevalence of enmity and hostility.” Goh Beng Lan’s “Globalization and Postcolonial Nation in Malaysia: Theoretical Challenges and Historical Possibilities” provides another dimension in understanding the role of nationalism in political life by relating this to globalization in postcolonial Malaysia. For Goh, there is no need to pit globalization against nationalism as there is a mutual constitution and reconstitution of the two as seen in the experience of Southeast Asian nations. Moreover, Western models are improvised in accordance to the specificities of the different societies. This is seen in Goh Beng Lan’s case study of Malaysian nationalism and the impact of capitalist localization and transnational Islamism. What has emerged is Malaysian nationalism, which integrates cultural and noncultural factors. An example she points out to is the country’s Vision 2020 launched in 1991, which sees Malaysia as a player in global capitalism and at the same time highlighting cultural pluralism that continued to persist with ethnicity and religion along with globalization and further consolidation of Malaysian nationalism. The process, however, has also not been smooth and can be seen in the tensions between Islamic nationalism and citizenship rights. By providing varying critical perspectives in examining culture and politics, these articles may be considered as signposts to alternative paradigms and discursive spaces that seek cultural solutions to political problems as well as in understanding how the sociopolitical could be better understood if cultural dynamics are deeply examined. This is particularly so when emphasis is placed on the relevance of indigenous over Western culture, on comprehending and resolving nationalist struggles based on a society’s history, and on how one’s nationalist identity need not be diminished and could even be enhanced in a globalized world.
Keywords: culture; politics